ПОРІВНЯЛЬНИЙ АНАЛІЗ АНТИКРИЗОВОГО ТА ЗАГАЛЬНОГО УПРАВЛІННЯ БУДІВЕЛЬНИМИ ПІДПРИЄМСТВАМИ (International Journal of Innovative Technologies in Economy, 2018)
The tools of strategic management can be used within the framework of crisis management. Modern concepts of crisis management consider the crisis not only as a situation requiring immediate overhaul, which is fully in line with the principles of actual strategic management in its implementation part, but also as a phenomenon focused on breaking the old and developing a new one, that is positive in essence.The need for anti-crisis management is determined by the goals and objectives of the management and socio-economic systems development of any level and inherent in the danger development of emerging crisis phenomena. Anti-crisis management as a category differs ambiguity, although many domestic and foreign scholars have contributed to its study. The ambiguity of crisis management is determined by the complex nature of any crisis, which, on the one hand, leads to devastating consequences, and, on the other, forms the conditions for further growth and qualitative improvement, overcoming the processes and phenomena that led to the emergence of the crisis.